Carbon-Neutral Infrastructure - Wentong Wang; Dongdong Yuan; Augusto Cannone Falchetto; Fucheng Guo (Buildings)
As global awareness of climate change intensifies, the significance of carbon neutrality has become increasingly evident and a pivotal sustainable development target for human society to pursue [...]